Potential Economic Value Of Nutritional Content Of Moringa Leaf Tea In Sikka Regency, East Nusa Tenggara - Wahyuni, Yuyun; Carcia, Maria Silvana Mariabel; Nunung, Agnes Yuniati; Se’do, Maria; Kopong, Rosalina; Nitit, Daniel Sera (Jurnal Projemen UNIPA, 2025)
Moringa (Moringa Oleifera) is a plant that is easily found in the surrounding environment and grows in Java, Sunda, Bali, Lampung, Madura, Sulawesi and Flores. In Flores, especially in Sikka Regency, moringa is a plant that is being cultivated. Moringa leaves also contain phytochemicals such as tannins, steroids, triterpenoids, flavonoids, saponins and alkaloids. These compounds have the ability as antibiotics, anti-inflammatory, detoxification and antibacterial drugs. One product that can be developed from moringa leaves is moringa tea. Moringa leaves can be used as a basic ingredient in making tea. In making tea, a drying process is carried out which aims to reduce the water content in the raw materials. This study aims to determine the nutritional content of moringa tea from several places in Sikka Regency so that it can help in the use of moringa as tea. This study was conducted in 3 locations for sampling moringa leaves, namely Talibura District, Alok Timur District and Paga District. The study used descriptive methods and laboratory tests on moringa tea. The results of the study were then compared with the quality parameters of tea according to the Indonesian National Standard (SNI) for tea. The output of the study is a national publication so that the community, especially in Sikka Regency, can use moringa leaves as a drink. The test was carried out at the Food Quality and Safety Laboratory, Faculty of Agricultural Technology, Brawijaya University, Malang. The results of the study showed differences in the nutritional content of moringa tea from the three locations. The highest protein content was in Paga District with a value of 25.86%, the highest fat content was in Talibura District with a value of 4.43%, water content was in Alok Timur District with a value of 8.42%, ash content in Paga District with a value of 8.20% and carbohydrate content in Alok Timur District with a value of 57.08%.